Hb Mozhaisk [β92(F8)His→Arg; HBB: c.278A>G] as a De Novo Mutation in a Child of Mixed Ethnic Origins. (2nd November 2017) - Benzoni, Elena; Giannone, Valentina; Michetti, Laura; Seia, Manuela; Cavalleri, Laura; Curcio, Cristina
Abstract: Approximately 150 variants described in the HbVar database have been found to be unstable and about 80.0% of these are on the β-globin gene. We describe the case of a 3-year-old child who presented at the emergency room with fever and asthenia. Hematological data suggested severe hemolytic anemia. Sequencing of the β-globin gene revealed the mutation HBB : c.278A>G at codon 92 in a heterozygous state, reported as Hb Mozhaisk in the HbVar database. Other family members did not have Hb Mozhaisk, thus, this variant is due to a de novo mutation. Because of the rarity of this globin variant, we believe it is important to report similar cases, to have a more complete phenotype description of the pathology and define an adequate reproductive risk for couples, considering the dominant inheritance pattern (hence an inheritance risk of 50.0%).